Novel Strategy of Lactide Polymerization Leading to Stereocomplex Polylactide Nanoparticles Using Supercritical Fluid Technology - Bibi, Gulnaz; Jung, Youngmee; Lim, Jong-Choo; Kim, Soo Hyun (American Chemical Society, 2016)
The enantiomeric crystallization of polylactides has removed the limitations of innate poor thermal and mechanical properties of the homopolymers. The supercritical fluid technology is an emerging panoramic version of biomedical polymer synthesis and has proven to be a domineering substitute to toxic organic solvents. Herein, we report an intriguing, efficient and a novel polymerization process using supercritical dimethyl ether (sc-DME) for preparation of polylactides leading to the stereocomplex polylactide (s-PLA) nanoparticles. The process has generated high molecular weight homopolymers (Mn >= 200 000 g mol(-1)) starting from monomers which ultimately crystallized to a dry powder of s-PLA nanoparticles. The optimum processing parameters are D/L-lactide polymerization using sc-DME at 130 degrees C, 400 bar for 5 h with a 30% monomer concentration, keeping the ratio [monomer]:[tin(II)2-ethylhexanoate]:[1-dodecanol] as 3000:1:1 while the stereocomplexation as sc-DME at 70 degrees C, 350 bar for 2 h. We have investigated the effects of monomer concentration, molecular weights of homopolymers, times, temperatures, and pressures on the degree of stereocomplexation. The degree of s-PLA was analyzed by DSC and XRD. The s-PLA has improved melting point and thermal degradation than homopolymers. The Young's modulus of s-PLA increased to 1.4 GPa with tensile strength (similar to 43 MPa) higher than homopolymers (similar to 13 MPa) with 3.2% elongation at break. The dry s-PLA powder shows a diversity of particle size ranging from 30 to 600 nm analyzed by SEM. The s-PLA finds potential applications in polymer nanofabrication, biomedical stents and encapsulation, melt-blending, solution casting, and molding.
Keywords: ENANTIOMERIC POLY(LACTIC ACID)S; DIMETHYL ETHER; PHASE-BEHAVIOR; BIODEGRADABLE POLYMERS; SPHERULITE GROWTH; CRYSTALLIZATION; PLA; CAST; POLY(L-LACTIDE); NANOSTRUCTURES